2019
DOI: 10.3390/ijerph17010154
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Total Mercury in Sediments of the Descoberto River Environmental Protection Area—Brazil

Abstract: To evaluate the total mercury accumulation (THg) in the Descoberto river basin environmental protection area (DREPA), nine sediment and water samples were collected from the Descoberto reservoir (lentic environment), and 23 in its tributaries (lotic environment), which are located in a densely urbanized area within the Descoberto river watershed, Brazil. The following physicochemical parameters of water were determined: dissolved oxygen (DO); hydrogen potential (pH); total dissolved solids (TDS); nitrate (NO3−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…Therefore, for the purposes of this study, globally accepted SQGs were used instead of ecotoxicological results [37][38][39][40] , and Average Shale Values (ASVs) were used instead of background values [41][42][43][44][45] . SQGs include criteria designed to assess sediment quality and the ecological risks associated with heavy metals 46 . The most widely used forms of empirical SQGs are based on sediment chemistry and biological effects, and on mechanistic techniques related to equilibrium partitioning 47 .…”
Section: Sediment Quality Guidelines (Sqgs)mentioning
confidence: 99%
“…Therefore, for the purposes of this study, globally accepted SQGs were used instead of ecotoxicological results [37][38][39][40] , and Average Shale Values (ASVs) were used instead of background values [41][42][43][44][45] . SQGs include criteria designed to assess sediment quality and the ecological risks associated with heavy metals 46 . The most widely used forms of empirical SQGs are based on sediment chemistry and biological effects, and on mechanistic techniques related to equilibrium partitioning 47 .…”
Section: Sediment Quality Guidelines (Sqgs)mentioning
confidence: 99%
“…There are prevalent examples of contamination of soil and water by mercury and other pollutants in mining regions in Brazil (Uryu et al 2001;Hylander et al 2006;Costa 2011;Ferreira Portela et al 2019) and other countries such as the United States (Stamenkovic et al 2004), Indonesia (Castilhos et al 2006) and China (Feng et al 2006). River contamination by mercury from gold extraction has directly and indirectly caused deaths among the indigenous Yanomami people, which has recently gained international media attention (Barbosa et al 1995;Vasconcellos et al 2018;Vega et al 2018).…”
Section: Contamination Riskmentioning
confidence: 99%
“…Regarding the potential risk of environmental pollution, not only terrestrial (SDG 15) and aquatic (SDG 14) ecosystems will be affected (Uryu et al 2001;Hylander et al 2006;Costa 2011;Ferreira Portela et al 2019;Gabriel et al 2020), but also drinking water availability (SDG 6; Mhlongo et al 2018) and health and well-being of local communities (SDG 2; Aguilera et al 2010;Johnston et al 2019). Considering such environmental and social consequences, some policy caveats need attention if the promises to achieve responsible consumption and production (SDG 12) and the establishment of sustainable cities and local communities (SDG 11) are to be attained.…”
Section: Risk To Sustainable Development Goalsmentioning
confidence: 99%
“…It also can be highly accumulated in river sediments due to adsorption and biotransformation ( Filistovic et al, 2015 , Ivanova et al, 2015 , Malikova et al, 2020 ). It is reported that the sediment uranium pollution has caused a serious hazard to aquatic ecosystems ( Sayadi et al, 2010 , Zahra et al, 2014 , Portela et al, 2020 ). The uranium level in the groundwater varies from one area to another ( Coyte and Vengosh, 2020 ).…”
Section: Introductionmentioning
confidence: 99%